At Westonci.ca, we connect you with experts who provide detailed answers to your most pressing questions. Start exploring now! Experience the ease of finding quick and accurate answers to your questions from professionals on our platform. Experience the convenience of finding accurate answers to your questions from knowledgeable experts on our platform.

What is the average rate of change of [tex][tex]$f(x)$[/tex][/tex] from [tex][tex]$x_1=2$[/tex][/tex] to [tex][tex]$x_2=4$[/tex][/tex]?

[tex]f(x) = \sqrt{3x + 1}[/tex]

Write your answer rounded to the nearest hundredth.


Sagot :

To find the average rate of change of the function [tex]\( f(x) = \sqrt{3x + 1} \)[/tex] from [tex]\( x_1 = 2 \)[/tex] to [tex]\( x_2 = 4 \)[/tex], we can follow these steps:

1. Evaluate the function at [tex]\( x_1 \)[/tex] and [tex]\( x_2 \)[/tex] to find [tex]\( f(x_1) \)[/tex] and [tex]\( f(x_2) \)[/tex]:

- [tex]\( f(x_1) = f(2) \)[/tex]
[tex]\[ f(2) = \sqrt{3 \cdot 2 + 1} = \sqrt{6 + 1} = \sqrt{7} \approx 2.6457513110645907 \][/tex]

- [tex]\( f(x_2) = f(4) \)[/tex]
[tex]\[ f(4) = \sqrt{3 \cdot 4 + 1} = \sqrt{12 + 1} = \sqrt{13} \approx 3.605551275463989 \][/tex]

2. Calculate the difference in the function values:

[tex]\[ f(x_2) - f(x_1) = f(4) - f(2) \approx 3.605551275463989 - 2.6457513110645907 = 0.9597999643993983 \][/tex]

3. Calculate the difference in the input values:

[tex]\[ x_2 - x_1 = 4 - 2 = 2 \][/tex]

4. Compute the average rate of change:

[tex]\[ \text{Average rate of change} = \frac{f(x_2) - f(x_1)}{x_2 - x_1} \approx \frac{0.9597999643993983}{2} = 0.4798999821996992 \][/tex]

5. Round the average rate of change to the nearest hundredth:

The average rate of change to the nearest hundredth is:
[tex]\[ \approx 0.48 \][/tex]

Thus, the average rate of change of [tex]\( f(x) = \sqrt{3x + 1} \)[/tex] from [tex]\( x_1=2 \)[/tex] to [tex]\( x_2=4 \)[/tex], rounded to the nearest hundredth, is [tex]\( 0.48 \)[/tex].